ASSOCIATION OF MODE OF DELIVERY AND DYSPAREUNIA: SYSTEMATIC REVIEW - Laurenso Lomi, Eldwin (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2022)
A condition that causes sexual activity to be unpleasant is one that impacts the health of a significant number of women. Dyspareunia is the term used to describe the ailment within the medical community. It is a challenging condition that, despite the intricacy of the issue, is routinely disregarded. It has also been shown that postpartum dyspareunia can occur at a variety of times following childbirth and over a variety of time periods. The percentage of people who are affected by the illness around the world ranges from 3 to 18 percent. The incidence of dyspareunia ranged from 30–60% in the first three months after giving birth, according to the findings of a study. However, this number reduced to 17–31% after six months had passed. The mode of birth, perineal damage, episiotomy, previous history of dyspareunia, breastfeeding, and the number of previous pregnancies are all considered to be risk factors for postpartum dyspareunia. In addition, a number of psychological problems, such as anxiety and depression, have been identified as significant factors in a number of studies. A number of studies have shown contradictory correlations, either between different associations or between different differences. Neither in regard to the method of distribution. Despite the findings of our study, the most common cause of dyspareunia is an aided or instrument-assisted vaginal birth.